The Activity of Extract from Rhizophora mucronata Endophytic Fungi Solid Fermentation Against Staphylococcus aureus and Enterobacter aerogenes - Wafa, Nurul; Yunianto, Prasetyawan; Widyaningsih, Tri Dewanti (Nusantara Science and Technology Proceedings, 2025)
Endophytic fungi, such as Rhizophora mucronata, can produce bioactive compounds from secondary metabolites that have the potential to become alternative antibiotics. This study aims to determine the activity of solid fermentation extract of mangrove endophytic fungi Rhizopora mucronata on the inhibition of bacteria Staphylococcus aureus and Enterobacter aerogenes. The extracts were fermented using rice media for 21 days and tested for antibacterial activity using disc diffusion method. Two of the five fermented extracts inhibited the growth of Staphylococcus aureus and Enterobacter aerogenes bacteria, namely codes ARM1M1 and DRM3M3. KLT-Bioautography was performed on isolate ARM1M1 to identify compounds that have antibacterial activity. Fermentation time variations were conducted at 0, 4, 8, 11, 14, 16, 18, 20, and 21 days. The disc diffusion method antibacterial test was carried out again to find out on which day of fermentation the extract actively inhibited bacterial activity and HPLC analysis was carried out to determine the retention time of the compound. As a result, Aspergillus sp. from Rhizophora mucronata code ARM1M1 showed the best inhibition against Staphylococcus aureus and Enterobacter aerogenes bacteria on day 20 of fermentation, with a retention time of 35 minutes, and an Rf value of 0.4.